Phosphoinositide-3-kinases p110α and p110β mediate S phase entry in astroglial cells in the marginal zone of rat neocortex - Müller, Rabea (Frontiers Media S.A., 2013)
In cells cultured from neocortex of newborn rats, phosphoinositide-3-kinases of class I regulate the DNA synthesis in a subgroup of astroglial cells. We have studied the location of these cells as well as the kinase isoforms which facilitate the S phase entry. Using dominant negative (dn) isoforms as well as selective pharmacological inhibitors we quantified S phase entry by nuclear labeling with bromodeoxyuridine (BrdU). Only in astroglial cells harvested from the marginal zone (MZ) of the neocortex inhibition of phosphoinositide-3-kinases reduced the nuclear labeling with BrdU, indicating that neocortical astroglial cells differ in the regulation of proliferation. The two kinase isoforms p110α and p110β were essential for S phase entry. p110α diminished the level of the p27(Kip1) which inactivates the complex of cyclin E and CDK2 necessary for entry into the S phase. p110β phosphorylated and inhibited glycogen synthase kinase-3β which can prevent S-phase entry. Taken together, both isoforms mediated S phase in a subgroup of neocortical astroglial cells and acted via distinct pathways.